Public Private Partnership success for a start-up [Rwanda] - Mvunabandi, Dominique (Technical Centre for Agricultural and Rural Cooperation, 2018)
The start-up enterprise Severe Weather Consult in Rwanda succeeded in receiving support to develop a business model and is now involved in a public private partnership that allows them to make use of weather data for an alert advisory service to farmers.